ENT600: Swim pro / Aina Zahirah Zaki … [et al.] - Zaki, Aina Zahirah; Aziz, Airin Fatehah; Roslan, Nurul Azra; Yahaya, Nurul Suryanie; Abd Latif, Siti Zarifah (2018)
It is known that everyone who swims is at risk of drowning regardless of their skills and in fact, the risk will much more higher among individual without swimming skills. There are a lot of factors contributed to incapability of swimming such as no swimming opportunities, lack of facilities and time constrain to attend swimming classes. This study was conducted to develop a product with a swim-assist technology to help individual who does not have the skill to swim. This product is an improvement from the current swimsuit in the market which is called The SMART swimsuit. It uses Functional Electrical Stimulation (FES) to stimulate the movement for swimming. This study also discovers how many potential consumers are interested with the product. Besides, the design of the product and reasoning behind the parameters chosen will be highlighted in this paper.